Inflation Through the Transmission Of Islamic And Conventional Monetary Policy In Indonesia - Rohmana, Yana; Utami, Suci Aprilliani (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2023)
This study aims to identify the transmission of Islamic and conventional monetary policy through the interest rate channel, credit channel, and exchange rate channel to inflation in Indonesia using the Vector Error Correction Model (VECM). VECM estimates show that all variables in the short term have no effect on inflation. The results of the Impulse-Response Function (IRF) show that all variables in the model are able to stabilize the inflation rate within three to seven months, while stabilizing real sector growth takes four to eight months. The results of the Forecast Error Variance Decomposition (FEVD) show that Total Conventional Banking Credit (CRED) has the most influence on inflation, while Bank Indonesia Certificate (SBI) is the variable that has the most influence on the real sector. Sharia monetary instruments play a big role in controlling inflation, but the effect is not as big as conventional monetary instruments. So that the relevant authorities are expected to develop more sharia monetary instruments based on the real sector based on underlying assets in order to be able to strengthen their influence on inflation.